Electrode, method for manufacturing electrode, and lithium secondary battery including electrode

By using gel polymer electrolyte in the electrode active material layer of the lithium secondary battery and curing the electrolyte in an oxygen environment with heat roller pressing technology, the safety problems of liquid electrolytes and the impregnation problems of gel electrolytes are solved, and a lithium secondary battery with high capacity and excellent lifespan is achieved.

CN119731802APending Publication Date: 2025-03-28LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380059928.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing lithium secondary batteries have safety risks in using liquid electrolytes, and gel electrolytes are difficult to completely cure and immerse in an oxygen environment, which affects the manufacturing efficiency and safety of the battery.

Method used

The electrode active material layer containing gel polymer electrolyte is adopted, and the electrolyte solution and oxygen-resisting member are mixed in the electrode slurry, and the electrolyte solution is thermally cured by a hot rolling method, thereby achieving complete curing and impregnation of the electrolyte in an oxygen environment.

Benefits of technology

It realizes the manufacture of lithium secondary batteries with high capacity and excellent life expectancy in an oxygen environment, improves the safety and manufacturing efficiency of the battery, and expands the selection range of electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731802A_ABST
    Figure CN119731802A_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode comprising an electrode current collector and an electrode active material layer disposed on at least one side of the electrode current collector, in which the electrode active material layer comprises an electrode active material and a gel polymer electrolyte, the electrode having a stiffness of 2 kPa to 4 kPa. Further, the present invention relates to a method of manufacturing an electrode, the method comprising the steps of applying an electrode slurry containing an electrolyte to an electrode current collector, disposing an oxygen barrier member on the electrode slurry coated with the electrode current collector, and hot rolling the electrode slurry covered with the oxygen barrier member, in which the electrolyte is cured by hot rolling.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0109522 filed in the Korean Intellectual Property Office on August 30, 2022, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to an electrode, a method for manufacturing the electrode, and a lithium secondary battery comprising the electrode. Background Art

[0004] In recent years, with the development of technology and the increase in demand for energy storage systems (ESS), the demand for batteries as energy sources has also increased dramatically, and research on batteries that can meet various needs has also been carried out. Specifically, lithium secondary batteries with high energy density and excellent life and cycle characteristics are being actively studied as power sources for such devices.

[0005] Generally, a lithium secondary battery comprises a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. As a common electrolyte for lithium secondary batteries, a liquid electrolyte in which a lithium salt is dissolved in a non-aqueous organic solvent is mainly used. However, the use of such a liquid electrolyte is likely to cause degradation of the electrode material and volatilization of the organic solvent, and also brings about the problem of combustion or explosion due to the increase in ambient temperature and the temperature of the battery itself and leakage, resulting in low safety.

[0006] Recently, research on various materials or types of solid electrolytes has been actively conducted to overcome the safety issues of liquid electrolytes. In particular, gel electrolytes can provide excellent stability and processability, and they also have gel phase adhesion, which can provide advantages such as excellent interface stability between electrodes and electrolytes.

[0007] Meanwhile, the gel electrolyte can be prepared by gelling (cross-linking) a composition in which a lithium salt, a solvent, a polymerizable monomer and an initiator are mixed at an appropriate temperature for a reasonable time. In this case, the gel electrolyte is not completely cured when the electrolyte is gelled in an oxygen environment. In addition, the gel electrolyte takes a considerable amount of time to be impregnated into the electrode. Therefore, in the process of manufacturing the battery, the gel electrolyte may volatilize or contact other electrodes to be separated. When the electrolyte is gelled in a space (such as a glove box) where an oxygen-free environment is set to prevent the above problems from occurring, it is difficult to manufacture a large electrode laminate due to the limitation of the space size.

[0008] Therefore, there is a need to develop a method for manufacturing large-area solid-state batteries by completely impregnating and curing a gel electrolyte even in an oxygen environment. Summary of the invention

[0009] Technical issues

[0010] One aspect of the present invention provides an electrode including an electrode active material layer containing a gel polymer electrolyte and having excellent capacity performance and lifespan performance.

[0011] Another aspect of the present invention provides a method for manufacturing an electrode having high capacity performance and excellent electrode stiffness by improving the problems of electrode impregnation and curing of a gel polymer electrolyte in an oxygen environment.

[0012] Technical Solution

[0013] According to one aspect of the present invention, there is provided an electrode comprising an electrode current collector and an electrode active material layer disposed on at least one side of the electrode current collector, wherein the electrode active material layer comprises an electrode active material and a gel polymer electrolyte, and the stiffness of the electrode is 2 kPa to 4 kPa.

[0014] According to another aspect of the present invention, a method for manufacturing an electrode is provided, the method comprising: applying an electrode slurry containing an electrolyte to an electrode current collector, disposing an oxygen barrier member on the applied electrode slurry, and hot rolling the electrode slurry covered with the oxygen barrier member, wherein the electrolyte is thermally cured by the hot rolling.

[0015] According to another aspect of the present invention, a lithium secondary battery including the electrode is provided.

[0016] Beneficial Effects

[0017] The electrode of the present invention comprises an electrode active material layer composited with a gel polymer electrolyte, so that its electrode stiffness satisfies a specific range. The electrode of the present invention comprises a gel polymer electrolyte impregnated inside the electrode active material layer, so it can have excellent capacity performance and high stiffness, thereby realizing a lithium secondary battery with improved output, safety and life performance at the same time.

[0018] In addition, the method for manufacturing an electrode of the present invention is different from the common technology of impregnating the electrolyte after manufacturing the electrode. The gel electrolyte is gelled under the condition that the electrode slurry and the electrolyte are mixed from the beginning, so the electrolyte can have improved electrode impregnation performance. Therefore, lithium precipitation and electrolyte volatilization will not occur due to the electrolyte not being impregnated, so a highly volatile electrolyte may become applicable, thereby expanding the range of electrolyte selection. In addition, the electrolyte can be cured in the process of manufacturing the electrode, so it is not necessary to inject the electrolyte and age it after the battery is assembled, thereby shortening the time of battery manufacturing. In addition, the method for manufacturing an electrode of the present invention solidifies the electrolyte by blocking the contact between the electrolyte and oxygen using an oxygen barrier member, so that the gel electrolyte can be completely solidified even in an oxygen environment. Therefore, it is possible to prevent the gel electrolyte from volatilizing or contacting other electrodes to be separated in the battery manufacturing process. In addition, electrolyte gelation and electrode manufacturing can be performed even in an oxygen environment, so that electrodes can be mass-produced through a roll-to-roll process. There is no need to gel the electrolyte in a space provided with an oxygen-free environment such as a glove box, so a large-area electrode can be manufactured. At the same time, in the present invention, the electrolyte contained in the electrode slurry is cross-linked by a thermal cross-linking method rather than a UV cross-linking method, so the electrolyte can be uniformly cured in the depth of the electrode where UV is difficult to penetrate. Therefore, even when a separate liquid electrolyte is not injected into the electrode laminate or the electrode loading thickness is not formed very thin when manufacturing a lithium secondary battery, gelation can occur uniformly throughout the electrode, so the lithium secondary battery can have improved capacity, yield and life. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a schematic cross-sectional view illustrating a detailed description of an electrode of the present invention;

[0020] Figure 2 is a graph measuring adhesion between the active material layer and the current collector in the negative electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 4, respectively; and

[0021] Figure 3 is a graph showing changes in capacity retention ratios of the lithium secondary batteries manufactured in Examples 1 to 3 and Comparative Examples 1 to 4 after driving at 45° C. with respect to the number of cycles. DETAILED DESCRIPTION

[0022] The advantages and features of the present invention and methods for implementing the same will be explained by the following embodiments described with reference to the accompanying drawings. However, the present invention can be implemented in different forms and should not be understood as being limited to the embodiments described herein. On the contrary, these embodiments are provided to make this disclosure full and complete, and to fully convey the scope of the present invention to those skilled in the art. In addition, the present invention is limited only by the scope of the claims. Throughout the specification, similar reference numerals represent similar components.

[0023] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by ordinary technicians in the field to which the invention belongs. Unless clearly and specifically defined, terms defined in commonly used dictionaries are not ideally or over-interpreted.

[0024] The terms used herein are not intended to limit the concepts of the present invention, but to describe embodiments. As used herein, the singular includes the plural, unless the context clearly indicates otherwise. The meaning of "comprises" and / or "comprising" used in this specification does not exclude the presence or addition of other components other than the mentioned components.

[0025] In the present specification, when an element “includes” a certain component, it may mean that the element does not exclude another component unless there is a clear contrary description, and may further include another component.

[0026] In this specification, the description "A and / or B" means A or B, or A and B.

[0027] As used herein, "%" means weight % unless otherwise specified.

[0028] The viscosity used herein can be measured using a viscometer, specifically, using a Brookfield viscometer (DV-II+ PRO Viscometer, Brookfield) as a viscometer, and measured at 25° C., a relative humidity (RH) of 50%, and a frequency of 30 Hz.

[0029] <Electrode>

[0030] In the following, reference will be made to Figure 1 The electrode of the present invention is described in detail. Figure 1 is a schematic cross-sectional view specifically illustrating an electrode of the present invention.

[0031] Specifically, the electrode 10 of the present invention includes an electrode current collector 110 and an electrode active material layer 120 disposed on at least one side of the electrode current collector, the electrode active material layer 120 includes an electrode active material and a gel polymer electrolyte, and the electrode has a rigidity of 2 kPa to 4 kPa.

[0032] Generally, the manufacturing method of the lithium secondary battery containing the gel polymer electrolyte is as follows: the electrode assembly containing the electrode and the separator is stored in the battery case, and then the composition (electrolyte) containing the cross-linkable material for forming the gel polymer electrolyte is injected into the battery case and solidified. For the lithium secondary battery manufactured by the above method, it is difficult to achieve the desired electrode rigidity due to the presence of unreacted cross-linkable material, and because it is difficult to fully impregnate the electrode with the formed gel polymer electrolyte to improve the lithium mobility, it is difficult to achieve the desired level of life performance and output performance.

[0033] In order to solve the above problems, the electrode active material layer 120 of the present invention in which the gel polymer electrolyte of the present invention is compounded is used, the electrode stiffness is set to a specific range, and the lithium mobility in the electrode is improved by impregnation and compounding with the gel polymer electrolyte, thereby facilitating capacity, output and life performance.

[0034] Electrode current collector (110)

[0035] The electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. Specifically, the electrode current collector may include at least one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, fired carbon, and aluminum-cadmium alloy. For example, when the electrode is a positive electrode, the electrode current collector may include aluminum, and when the electrode is a negative electrode, the electrode current collector may include copper.

[0036] For example, the electrode current collector can be used in various forms, such as films, sheets, foils, nets, screens, porous bodies, foams, and nonwoven fabrics. Specifically, the electrode current collector can include a polymer layer and a metal layer disposed on both sides of the polymer layer, and the metal layer can include at least one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, fired carbon, and aluminum-cadmium alloy.

[0037] Electrode active material layer (120)

[0038] The electrode active material layer 120 may be disposed on at least one side of the electrode current collector. Specifically, the electrode active material layer 120 may be disposed on one side or both sides of the electrode current collector.

[0039] The electrode active material layer 120 includes an electrode active material and a gel polymer electrolyte. Specifically, the electrode active material layer 120 may be a gel polymer electrolyte composite electrode active material layer composited with an electrode active material and a gel polymer electrolyte. Specifically, the gel polymer electrolyte may be impregnated in the electrode active material layer 120. The gel polymer electrolyte may be disposed inside the electrode active material layer 120 or inside and on the surface of the electrode active material layer 120.

[0040] The gel polymer electrolyte may be a solidified product of an electrolyte containing a cross-linkable material, a lithium salt and an organic solvent. The electrolyte may be a composition for forming a gel polymer electrolyte. The electrolyte may further contain an initiator.

[0041] The cross-linkable material may include at least one selected from a cross-linkable monomer (hereinafter referred to as “monomer”) and a cross-linkable oligomer (hereinafter referred to as “oligomer”).

[0042] The monomer and / or oligomer is a material that can form a gel polymer electrolyte through a polymerization reaction.

[0043] The monomer may be selected from the group consisting of ethylene glycol diacrylate, triethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate (ETPTA), bisphenol A ethoxylated dimethacrylate, acrylic acid, carboxyethyl acrylate, methyl cyanoacrylate, ethyl cyanoacrylate, ethyl cyanoethoxyacrylate, cyanoacrylic acid, hydroxyethyl methacrylate, hydroxypropyl acrylate, derivatives thereof or combinations thereof, but is not limited thereto.

[0044] The oligomer may include at least one selected from the group consisting of polyether oligomers, polycarbonate oligomers, acrylate oligomers, polysiloxane oligomers, phosphazene oligomers, polyethylene oligomers, polyurethane oligomers, epoxy oligomers, fluorine oligomers, polyethylene oxide, polyester sulfide, polyvinyl alcohol and polyvinylidene fluoride. Specifically, the oligomer may include at least one selected from the group consisting of fluorine oligomers, polycarbonate oligomers and polysiloxane oligomers.

[0045] Relative to 100 parts by weight of electrolyte, the content of monomer and / or oligomer can be 4 parts by weight to 40 parts by weight, specifically 5 parts by weight to 40 parts by weight, more specifically 5 parts by weight to 30 parts by weight. When the amount of monomer and / or oligomer is less than 4 parts by weight relative to 100 parts by weight of electrolyte, the adhesion between the current collector and the electrode active material layer is reduced due to the insufficient cross-linking reaction between the monomer and / or oligomer. In addition, when the amount of monomer and / or oligomer is greater than 40 parts by weight relative to 100 parts by weight of electrolyte, the resistance of the electrode increases.

[0046] Lithium salts are used as media for transporting ions in lithium secondary batteries.

[0047] Lithium salt is a material that is easily dissolved in the gel polymer electrolyte, and may include, for example, a single substance or a mixture of two or more substances selected from the group consisting of: LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, LiFSI, LiTFSI, LiB(CO2O4)2, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate and lithium imide, but are not limited to these.

[0048] The concentration of the lithium salt in the electrolyte may be 0.1 M to 5.0 M, preferably 0.1 M to 3.0 M, and more preferably 0.2 M to 3.0 M. When the content of the lithium salt is within the above range, the solidified electrolyte may have sufficient ion conductivity.

[0049] The organic solvent is used to dissolve the above-mentioned monomers and / or oligomers, initiator and lithium salt.

[0050] Organic solvents are commonly used solvents in secondary batteries. For example, ethers, esters (acetates, propionates), amides, linear carbonates or cyclic carbonates, nitriles (acetonitrile, SN, etc.) can be used alone or in combination of two or more.

[0051] In particular, a carbonate-based solvent including a carbonate compound of a cyclic carbonate, a linear carbonate or a mixture thereof may be generally used.

[0052] The specific example of cyclic carbonate compound includes a single compound or a mixture of at least two compounds selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate and its halide. In addition, as a specific example of linear carbonate compound, a single compound or a mixture of at least two compounds selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) can be used, but embodiments of the present invention are not limited thereto.

[0053] In particular, among carbonate solvents, propylene carbonate and ethylene carbonate are preferably used as cyclic carbonates because they are high-viscosity organic solvents and have a high dielectric constant, thereby satisfactorily dissociating the lithium salts in the electrolyte. When such cyclic carbonates are mixed with low-viscosity, low-dielectric-constant straight-chain carbonates (such as ethyl methyl carbonate, diethyl carbonate or dimethyl carbonate) in an appropriate proportion and used, an electrolyte with higher conductivity can be prepared. Therefore, it is more preferred to use such a mixture.

[0054] In addition, as the ester in the organic solvent, a single compound or a mixture of at least two selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, α-valerolactone and ε-caprolactone can be used, but the embodiments of the present invention are not limited thereto.

[0055] Initiator is a material for forming active free radicals and thus causing the polymerization reaction of monomers and / or oligomers. Specifically, the initiator can be decomposed by light (e.g., UV) at room temperature (5°C to 30°C), or by thermal decomposition at 30°C to 100°C to form free radicals, thereby initiating the free radical polymerization reaction of monomers and / or oligomers.

[0056] The initiator may be a thermal curing initiator. For example, the initiator may include at least one selected from the group consisting of benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, tert-butyl peroxide (2-ethylhexanoate), cumene hydroperoxide, hydrogen peroxide, 2,2'-azobis (2-cyanobutane), 2,2'-azobis (methylbutyronitrile), 2,2'-azobis (isobutyronitrile) (AIBN) and 2,2'-azobis (dimethyl) valeronitrile (AMVN).

[0057] The content of the initiator may be 0.01 wt % to 10 wt %, specifically 0.05 wt % to 7 wt %, more specifically 0.06 wt % to 5 wt %, relative to 100 parts by weight of the monomer and / or oligomer. When the content of the initiator is within the above range, an active cross-linking reaction may occur between the monomer and / or oligomer to obtain adhesion between the current collector and the electrode active material layer, and the polymerization rate in the electrolyte may be controlled, thereby preventing the unreacted initiator from remaining and adversely affecting the battery performance.

[0058] The electrode stiffness of the electrode 10 is 2 kPa to 4 kPa. When the electrode stiffness of the electrode 10 is within the above range, it can be understood that the electrode active material layer 120 has been fully impregnated with the gel polymer electrolyte. When the electrode stiffness of the electrode 10 is less than 2 kPa, it can be assessed that the gel polymer electrolyte is not sufficiently impregnated with the electrode active material layer 120, or that unreacted or uncured cross-linkable materials (cross-linkable monomers, cross-linkable oligomers, etc.) are present at a level higher than required, in which case, it may lead to reduced lithium mobility, capacity performance failure, and generation of side reaction gases, etc. When the electrode stiffness of the electrode 10 is greater than 4 kPa, the resistance becomes too high, so the desired output performance and life performance may not be achieved, and the brittleness of the electrode itself is reduced, resulting in the generation of foreign matter due to damage to the electrode edge, and the resulting internal short circuit.

[0059] Electrode stiffness can be measured using a universal testing machine (UTM). Specifically, electrode stiffness can refer to the maximum stiffness measured by fastening the electrode to an aluminum (Al) fixture with a hole of 5 cm in diameter and then pressing the electrode with a metal rod of 2 cm in diameter using a UTM device. Electrode stiffness is measured by pressing the electrode with a metal rod, and therefore will not be significantly affected by the area, thickness, loading amount, etc. of the electrode.

[0060] There is no particular limitation on the method for achieving the above-mentioned electrode stiffness range, and for example, the following methods may be applicable: using a mixture of an electrode active material and an electrolyte (a composition for forming a gel polymer electrolyte) as an electrode slurry used when manufacturing an electrode active material; replacing the binder in the electrode slurry with a gel polymer electrolyte, using an oxygen barrier member to manufacture an electrode active material layer by a hot rolling method, and using the method for manufacturing an electrode described later.

[0061] The electrode can be a positive electrode or a negative electrode.

[0062] When the electrode is a positive electrode, the electrode active material layer may be a positive electrode active material layer, and the electrode active material may be a positive electrode active material.

[0063] Lithium transition metal oxides can be used as positive electrode active materials and can be used without limitation as long as the insertion and extraction of lithium ions can be easily achieved during charging and discharging. For example, the positive electrode active material can be at least one selected from lithium nickel cobalt composite oxides, lithium manganese composite oxides and lithium iron phosphate composite oxides.

[0064] Specifically, the positive electrode active material may include a lithium nickel cobalt-based composite oxide represented by Formula 1 below.

[0065] [Formula 1]

[0066] Li 1+x (Ni a Co b Mn c M d )O2

[0067] In the above formula 1,

[0068] M is at least one selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and

[0069] 1+x, a, b, c and d are the molar ratios of the individual elements, and

[0070] Satisfy -0.2 ≤ x ≤ 0.2, 0.60 ≤ a < 1, 0 < b ≤ 0.30, 0 < c ≤ 0.30, 0 ≤ d ≤ 0.10, a + b + c + d = 1.

[0071] The above 1 + x represents the molar ratio of lithium in the lithium nickel cobalt composite oxide, which can satisfy -0.1 ≤ x ≤ 0.2, or 0 ≤ x ≤ 0.2. When the molar ratio of lithium satisfies the above range, the lithium nickel cobalt composite oxide can have a crystal structure stably formed.

[0072] The above a represents the molar ratio of nickel in the lithium nickel cobalt composite oxide relative to all metals except lithium, which can satisfy 0.70 ≤ a < 1, 0.75 ≤ a < 1 or 0.80 ≤ a < 1. When the molar ratio of nickel satisfies the above range, a relatively high energy density is presented, and thus high capacity can be achieved.

[0073] The above b represents the molar ratio of cobalt in the lithium nickel cobalt composite oxide relative to all metals except lithium, which can satisfy 0 < b ≤ 0.20, 0 < b ≤ 0.15 or 0 < b ≤ 0.10. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be achieved.

[0074] The above c represents the molar ratio of manganese in the lithium nickel cobalt composite oxide relative to all metals except lithium, which can satisfy 0 < c ≤ 0.20, 0 < c ≤ 0.15 or 0 < c ≤ 0.10. When the molar ratio of manganese satisfies the above range, the positive electrode active material can exhibit excellent structural stability.

[0075] In one embodiment of the present invention, the lithium nickel cobalt composite metal oxide may include at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and Al may be preferably included as the doping element. That is, d representing the molar ratio of the doping element in the lithium composite transition metal oxide relative to all metals except lithium can satisfy 0 < d ≤ 0.10, 0 < d ≤ 0.08 or 0 < d ≤ 0.05.

[0076] Preferably, a, b, c, and d can respectively satisfy 0.70 ≤ a ≤ 1, 0 < b ≤ 0.2, 0 < c ≤ 0.2, 0 ≤ d ≤ 0.1.

[0077] The lithium manganese composite oxide may be at least one selected from the group consisting of: Li p Mn 1-q M q A2, Li p Mn2O 4-r X r 、Li p Mn2-q M q M' r A4, Li p Co 1-q M q A2.Li p Co 1-q M q O 2-r X r , Li p Ni 1-q M q O 2-r X r , Li p Ni 1-q Co q O 2- r X r , Li p Ni 1-q-r Co q M r A w , Li p Ni 1-q-r Co q M r O 2-w X w , Li p Ni 1-q-r Mn q M r A w and Li p Ni 1-q-r Mn q M r O 2-w X w In this case, p, q, r and w satisfy 0.9≤p≤1.2, 0≤q≤1, 0≤r≤1 and 0≤w≤2 respectively, M and M' are the same or different and are at least one element selected from the group consisting of Mg, Al, Co, K, Na, Ca, Si, Ti, Sn, V, Ge, Ga, B, As, Zr, Mn, Cr, Fe, Sr, V and rare earth elements, A is at least one element selected from the group consisting of O, F, S and P, and X is at least one element selected from the group consisting of F, S and P.

[0078] The lithium iron phosphate-based composite oxide can be represented by Formula 2 below.

[0079] [Formula 2]

[0080] LiFe 1-x M x PO4

[0081] In the above formula 2,

[0082] M is at least one selected from Ni, Co, Mn, Al, Mg, Y, Zn, In, Ru, Sn, Sb, Ti, Te, Nb, Mo, Cr, Zr, W, Ir and V, and satisfies 0≤x<1.

[0083] The content of the positive electrode active material in the positive electrode active material layer may be 80 wt % to 99 wt %, specifically 90 wt % to 99 wt %.

[0084] The positive electrode active material layer may further contain a conductive material.

[0085] In addition, the conductive material is a material that provides conductivity without causing chemical changes in the battery, and may be added to the positive electrode active material layer in an amount of 0.5 wt % to 20 wt %.

[0086] For example, the conductive material can be selected from the following conductive materials, such as: carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; graphite powder, such as natural graphite, artificial graphite, carbon nanotubes and graphite; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as fluorinated carbon powder, aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives.

[0087] The positive electrode active material layer may further include a binder.

[0088] The binder is a component that helps the bonding between the active material and the conductive material and the current collector, and can be added to the positive electrode active material layer in an amount of 1% to 30% by weight. Examples of such binders may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0089] When the electrode 10 is a positive electrode, the electrode stiffness of the electrode may be 2 kPa to 4 kPa, specifically 2.5 kPa to 3.5 kPa, more specifically 2.75 kPa to 3.25 kPa, and even more specifically 2.75 kPa to 2.85 kPa.

[0090] When the electrode is a negative electrode, the electrode active material layer may be a negative electrode active material layer, and the electrode active material may be a negative electrode active material.

[0091] The negative electrode active material may include at least one selected from the group consisting of: carbonaceous materials capable of reversibly intercalating / deintercalating lithium ions, metals or alloys of lithium and these metals, metal composite oxides, materials capable of being doped and dedoped with lithium, lithium metal, and transition metal oxides, and may preferably be a carbon material.

[0092] As the carbonaceous material capable of reversibly intercalating / deintercalating lithium ions, any carbon material can be used without particular limitation as long as it is a carbonaceous negative electrode active material commonly used in lithium ion secondary batteries. As common examples, crystalline carbon, amorphous carbon, or both of them can be used. Examples of crystalline carbon can be graphite, such as irregular, planar, flaky, spherical, or fibrous natural graphite or artificial graphite. Examples of amorphous carbon can be soft carbon (low-temperature fired carbon), hard carbon, mesophase pitch carbide, fired coke, etc.

[0093] As the metal or the alloy of these metals and lithium, metals selected from the group consisting of: Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or alloys of these metals and lithium can be used.

[0094] As the metal composite oxide, at least one selected from the group consisting of PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0 ≤ x ≤ 1), Li x WO2(0 ≤ x ≤ 1), and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups 1, 2, and 3 of the periodic table, or halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) can be used.

[0095] The material capable of being doped and dedoped with lithium may include Si, SiO x(0 < x ≤ 2), Si-Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Si), Sn, SnO2, and Sn-Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Sn), a mixture of SiO2 and at least one of them can be used. Element Y can be selected from the group consisting of: Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0096] Examples of transition metal oxides can include lithium-containing titanium composite oxide (LTO), vanadium oxide, and lithium vanadium oxide.

[0097] The content of the negative electrode active material in the negative electrode active material layer can be 80% to 99% by weight.

[0098] The negative electrode active material layer can also contain a conductive material.

[0099] In addition, the conductive material is a material that provides conductivity without causing chemical changes in the battery, and can be added to the negative electrode active material layer in an amount of 0.5% to 20% by weight.

[0100] For example, the conductive material can be selected from the following conductive materials, such as: carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking carbon black; graphite powder, such as natural graphite, artificial graphite, carbon nanotubes, and graphite; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives.

[0101] The negative electrode active material layer can also contain a binder.

[0102] The binder is a component that helps the bonding between the active material and the conductive material and the current collector, and can usually be added to the negative electrode active material layer in an amount of 1% to 30% by weight. Examples of such binders may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0103] When the electrode 10 is a negative electrode, the electrode stiffness of the electrode may be 2 kPa to 4 kPa, specifically 2 kPa to 3 kPa, and more specifically 2.1 kPa to 2.7 kPa.

[0104] In the present invention, the electrode active material layer (positive electrode active material layer or negative electrode active material layer) may not contain a binder. As described above, the electrode active material layer of the present invention contains a solidified product of a gel polymer electrolyte or an electrolyte (a composition for forming a gel polymer electrolyte), and the gel polymer electrolyte can replace the binder. In view of the fact that the stiffness of the electrode active material layer may be excessively increased or become an unfavorable factor of resistance depending on the binder used, the gel polymer electrolyte can be used to bond the electrode active material and / or the electrode current collector, and can also improve the lithium migration performance.

[0105] The thickness of the electrode 110 or the electrode active material layer 120 may be 50 μm to 1000 μm, specifically 50 μm to 500 μm, and more specifically 50 μm to 300 μm.

[0106] In the present invention, the electrode 10 may further include a coating layer 130. The coating layer 130 may be disposed on a surface of the electrode 10, specifically, on a side opposite to a side of the electrode active material layer 120 facing the electrode current collector 110.

[0107] The coating layer 130 may contain a gel polymer electrolyte. Specifically, the coating layer 130 may be formed of only a gel polymer electrolyte.

[0108] The gel polymer electrolyte contained in the coating layer 130 may be the same as the gel polymer electrolyte contained in the electrode active material layer 120 .

[0109] The gel polymer electrolyte contained in the coating layer 130 may mean a gel polymer electrolyte formed on the surface of the electrode active material layer when forming the gel polymer electrolyte contained in the electrode active material layer.

[0110] [Method for producing electrode]

[0111] In addition, the present invention provides a method for manufacturing an electrode. The method for manufacturing an electrode may be the above-mentioned method for manufacturing an electrode.

[0112] The method for manufacturing an electrode of the present invention comprises: applying an electrode slurry containing an electrolyte to an electrode current collector, placing an oxygen barrier member on the applied electrode slurry, and hot rolling the electrode slurry covered with the oxygen barrier member, wherein the electrolyte is thermally cured by hot rolling. In this case, the electrode manufactured by the above method can be a positive electrode or a negative electrode.

[0113] According to the present invention, unlike the typical technique of impregnating the electrolyte after manufacturing the electrode, the gel electrolyte is gelled under the condition that the electrode slurry and the electrolyte are mixed from the beginning, so the electrolyte can have improved electrode impregnation performance. Therefore, lithium precipitation and electrolyte volatilization caused by the electrolyte not being impregnated will not be caused, so high volatility electrolytes may become applicable, thereby expanding the range of electrolyte selection. In addition, the electrolyte can be solidified in the process of manufacturing the electrode, so it is not necessary to inject the electrolyte and perform aging after the battery is assembled, thereby shortening the battery manufacturing time.

[0114] According to the present invention, the electrolyte is solidified by blocking the contact between the electrolyte and oxygen using an oxygen-blocking member, so that the gel electrolyte can be completely solidified even in an oxygen environment. Therefore, the gel electrolyte can be prevented from volatilizing or contacting other electrodes to be separated during the battery manufacturing process. In addition, the electrolyte gelation and electrode manufacturing can be performed even in an oxygen environment, so that the electrodes can be mass-produced by a roll-to-roll process. There is no need to gel the electrolyte in a space where an oxygen-free environment is set, such as a glove box, so that large-area electrodes can be manufactured.

[0115] At the same time, in the present invention, the electrolyte contained in the electrode slurry is cross-linked by a thermal cross-linking method rather than a UV cross-linking method. Therefore, the electrolyte can be uniformly cured in the depth of the electrode where UV is difficult to penetrate. Therefore, even when a separate liquid electrolyte is not injected into the electrode laminate or the electrode load thickness is not formed very thin when manufacturing a lithium secondary battery, gelation can occur uniformly throughout the electrode, so the lithium secondary battery can have improved capacity, output and life.

[0116] (1) Apply the electrode slurry containing the electrolyte to the electrode current collector

[0117] First, the method of manufacturing an electrode of the present invention begins with coating an electrode slurry onto an electrode current collector.

[0118] The coated electrode slurry can form an electrode active material layer by a hot rolling process described later. Rolling is hot rolling and is carried out in the presence of an oxygen barrier member, so a gel polymer electrolyte with a high curing rate can be present in the electrode active material layer without any residual unreacted cross-linkable substance. The electrode active material layer prepared therefrom has an appropriate level of electrode stiffness, so a lithium secondary battery with excellent stiffness and improved capacity performance, output performance and life performance can be obtained.

[0119] The electrode current collector is as described above.

[0120] Then, the electrode slurry of the present invention includes an electrolyte. In this case, the electrolyte may be a composition for forming a gel polymer electrolyte. Specifically, the electrolyte may include a crosslinkable material, a lithium salt, and an organic solvent. The electrolyte may also include an initiator. The detailed description of the electrolyte, the crosslinkable material, the lithium salt, the organic solvent, and the initiator is as described above.

[0121] The electrode slurry may further include an electrode active material. The electrode active material may be a positive electrode active material or a negative electrode active material. In addition, the electrode slurry may further include a conductive material and / or a binder. The description of the electrode active material, the conductive material and the binder is the same as described above.

[0122] Meanwhile, the electrode slurry of the present invention may not contain a binder. In this case, the binder is a common binder used in common electrode manufacturing, and refers to materials such as polyvinylidene fluoride (PVDF).

[0123] The thermally cured electrolyte polymer in the electrode of the present invention can replace the binder to support the combination of the active material and the conductive material and the current collector. The electrode slurry does not contain the binder, so the electrode resistance is relatively reduced.

[0124] The electrode slurry of the present invention may not contain any solvent other than the organic solvent of the electrolyte. Specifically, the electrode slurry may not contain N-methyl-2-pyrrolidone (NMP). Typically, an electrode active material layer is formed by the electrode slurry and then impregnated with an electrolyte to manufacture an electrode. In this case, in the process of preparing the electrode active material layer, drying and rolling processes are performed respectively to remove the N-methyl-2-pyrrolidone (NMP) solvent contained in the electrode slurry, especially during the rolling process, the active material is damaged, thereby reducing the service life of the battery. However, the present invention uses a mixture of active material and conductive material in the electrolyte, instead of impregnating the electrode active material layer with the electrolyte, so the drying and rolling processes for forming the active material layer are omitted, thereby minimizing damage to the active material.

[0125] The solid content of the electrode slurry can be 30% to 80%, specifically 40% to 80%, and more specifically 50% to 80%. When the solid content of the electrolyte satisfies the above numerical range, the solidified electrolyte is included in the electrode in a suitable amount, thereby improving the electrode processability and optimizing the battery performance.

[0126] In addition, when the solid content of the electrolyte satisfies the above numerical range, the electrode slurry may have a viscosity suitable for the electrode current collector. For example, at 25° C., the viscosity of the electrode slurry may be 20,000 cP or less, specifically 3,000 cP to 15,000 cP, and more specifically 4,000 cP to 12,000 cP.

[0127] As a method for mixing the electrode slurry containing the electrolyte solution, a common mixing method can be used. For example, the electrode slurry containing the electrolyte solution can be mixed by stirring it with a homogenizer.

[0128] As a coating method of the electrode slurry containing the electrolyte, a common coating method can be used, such as rod coating, spin coating, roller coating, slot die coating, manual coating, spray coating, etc., and one of the methods or a combination of two or more methods can be used.

[0129] (2) Placing an oxygen barrier on the coated electrode slurry

[0130] Then, an oxygen barrier member is disposed on the coated electrode slurry. The electrode slurry may be covered with an oxygen barrier member, so that contact between the electrolyte contained in the electrode slurry and oxygen may be blocked. In addition, when there is no oxygen barrier member on the electrode slurry, when the electrode slurry is rolled, the electrode slurry may remain on the rolled member, thereby reducing the processability and causing the thickness and load of the produced electrode to be inconsistent.

[0131] The oxygen barrier member may be insoluble in the solvent to effectively block the contact between the electrolyte and oxygen. Specifically, the oxygen barrier member may be insoluble in the organic solvent. In addition, the oxygen barrier member may include a material having flexibility so that it can be wound on a roll together with the electrode.

[0132] For example, the oxygen barrier member may include at least one selected from the group consisting of polypropylene (PP) and high-density polyethylene (HDPE), but is not limited thereto.

[0133] The thickness of the oxygen barrier member may be 20 to 2000 μm, specifically 50 to 500 μm, and more specifically 50 to 200 μm. When the thickness of the oxygen barrier member satisfies the above numerical range, contact between the electrolyte and oxygen may be blocked, so that the electrolyte may be completely solidified.

[0134] (3) Hot rolling of the electrode slurry covered with the oxygen barrier member

[0135] Then, the electrode slurry covered with the oxygen barrier member is subjected to heat roll pressing. In this case, the electrolyte contained in the electrode slurry is thermally cured by the heat roll pressing.

[0136] The thermal curing of the electrolyte can be performed by heating the electrolyte covered with the oxygen barrier member, so that the cross-linkable material (monomer and / or oligomer) contained in the electrolyte is cross-linked. The electrolyte is cured while the contact between the electrolyte and oxygen is blocked by the oxygen barrier member, thereby preventing the electrolyte from volatilizing or contacting other electrodes to be separated.

[0137] According to the present invention, the hot rolling may include rolling the electrode slurry with a press roller. The hot rolling of the electrode slurry using the press roller may be performed to thermally cure the electrolyte contained in the electrode slurry.

[0138] The surface temperature of the press roller may be 30 to 80° C., specifically 40 to 80° C., more specifically 50 to 70° C. When the surface temperature of the press roller satisfies the above numerical range, the temperature condition for crosslinking the electrolyte without damaging the oxygen barrier member can be achieved.

[0139] According to the present invention, the gap between the pressing roller and the electrode slurry can be adjusted to control the electrode loading thickness. The capacity of the lithium secondary battery containing the electrode manufactured by the present invention can be adjusted by controlling the electrode loading thickness.

[0140] After the hot rolling, the electrolyte impregnated in the electrode and the electrolyte present on the electrode surface may solidify. In this case, the electrolyte present on the electrode surface may be solidified by the hot rolling, thereby forming an electrolyte layer (such as Figure 1 The coating 130 in FIG.

[0141] The electrolyte layer may include a polymer matrix formed by cross-linking a monomer and / or oligomer and an initiator, and a lithium salt impregnated into the polymer matrix. In this case, the electrolyte layer includes the lithium salt and thus may have ion conductivity.

[0142] The curing degree of the electrolyte layer may be 93% to 100%, specifically 95% to 100%, and more specifically 98% to 100%. When the curing degree of the electrolyte layer satisfies the above range, a uniform thickness of the electrolyte layer can be formed on the active material layer, and the problem of separation of the electrolyte layer from the active material layer can be prevented.

[0143] The thickness of the electrolyte layer may be 1 μm to 200 μm, specifically 5 μm to 150 μm, and more specifically 5 μm to 80 μm. When the thickness of the electrolyte layer satisfies the above numerical range, the electrolyte layer can be prevented from being separated from the active material layer, and the cation (Li +) can be easily passed and the performance degradation depending on the total volume of the lithium secondary battery can be minimized.

[0144] After hot rolling, the thickness of the electrode or electrode active material layer may be 50 μm to 1000 μm, specifically 50 μm to 500 μm, and more specifically 50 μm to 300 μm. When the thickness of the electrode is less than 50 μm, the battery capacity may be reduced due to insufficient electrode load thickness. In addition, when the thickness of the electrode is greater than 1000 μm, the ion conduction path becomes longer, resulting in poor battery output performance, and the electrolyte in the electrode slurry may not be uniformly solidified because the heat cannot reach deep inside the electrode slurry.

[0145] (4) Heating the electrode after hot rolling

[0146] The method for manufacturing an electrode of the present invention may further include heating the electrode after hot rolling. The electrolyte in the electrode may be further thermally cured by heating the electrode.

[0147] Heating may include storing the electrode at a temperature of 40° C. to 80° C. for 10 minutes to 24 hours.

[0148] In this case, the temperature may be 40° C. to 80° C., specifically 50° C. to 80° C., and more specifically 60° C. to 70° C. In order to solidify the unsolidified electrolyte in the electrode slurry while stabilizing the remaining components contained in the electrode slurry, it is desirable to control the storage temperature within the above numerical range.

[0149] Furthermore, the storage time may be 10 minutes to 24 hours, specifically 1 hour to 10 hours, and more specifically 1 hour to 5 hours.

[0150] When the storage time is less than 10 minutes, the temperature inside the battery does not rise enough, resulting in curing failure, while when the storage time exceeds 24 hours, some additives in the battery may decompose.

[0151] This storage may correspond to storing the electrode roll wound with the current collector / electrode slurry / oxygen barrier member stacked in sequence in the high temperature chamber. Therefore, even when the high temperature chamber is evacuated, the volatilization of the electrolyte in the electrode can be minimized. In addition, the space in the chamber can be fully utilized to improve the electrode productivity.

[0152] A vacuum state can be formed in the high temperature chamber. In this case, the oxygen in the chamber can be removed to complete the solidification of the electrolyte in a shorter time.

[0153] Meanwhile, after the solidification of the electrolyte is completed, the oxygen blocking member disposed on the electrode may be removed.

[0154] <Lithium Secondary Battery>

[0155] In addition, the present invention provides a lithium secondary battery comprising the electrode.

[0156] Specifically, the lithium secondary battery may include an electrode assembly including two or more electrodes. The electrode assembly may be formed by a stack of two or more electrodes.

[0157] At least one of the two or more electrodes may be the above-mentioned electrode. Specifically, the two or more electrodes may all be the above-mentioned electrodes. The electrode assembly may be formed by alternately stacking at least one positive electrode and at least one negative electrode, and the positive electrode and the negative electrode may be the above-mentioned electrodes. In the electrode assembly, the positive electrode active material layer of the positive electrode may face the negative electrode active material layer of the negative electrode, the positive electrode active material layer of the positive electrode may face the coating of the negative electrode, or the coating of the positive electrode may face the negative electrode active material layer of the negative electrode, or the coating of the positive electrode may face the coating of the negative electrode.

[0158] According to one embodiment of the present invention, the lithium secondary battery of the present invention may not include a separator disposed between the positive electrode and the negative electrode in a conventional lithium secondary battery. Specifically, the electrolyte layer (coating) formed on the surface of the electrode of the present invention may be disposed between the positive electrode and the negative electrode, and thus may be used as a conventional separator.

[0159] According to another embodiment of the present invention, the lithium secondary battery of the present invention may include a separator. In this case, the separator may be immersed in an electrolyte and then cured (e.g., UV cured) to cure the electrolyte in the pores. Compared with the electrode, the thickness of the separator is relatively thin, so the curing of the electrolyte contained in the pores is easy to proceed.

[0160] In addition, the lithium secondary battery of the present invention may not contain a liquid electrolyte injected when manufacturing a conventional lithium secondary battery. Specifically, the above electrolyte of the present invention can be uniformly solidified in the electrode, and thus can be used as a conventional liquid electrolyte.

[0161] The lithium secondary battery of the present invention can be manufactured by placing the above-mentioned electrode assembly in a cylindrical battery case or a square battery case and sealing the case. The battery case can be a battery case commonly used in the art, and the shape is not limited according to the use of the battery, for example, it can be cylindrical, square, pouch or coin-shaped, but not limited thereto.

[0162] The lithium secondary battery of one embodiment of the present invention can be used as a battery cell used as a power source for small-sized devices, and can also be preferably used as a unit cell in a large- and medium-sized battery module containing a plurality of battery cells. Preferred examples of large- and medium-sized devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems (ESS).

[0163] Hereinafter, the present invention will be further described in detail by specific embodiments. However, the embodiments shown below are only used to understand the present invention, and the scope of the inventive concept is not limited thereto. It is obvious to those skilled in the art that various modifications and variations can be made within the scope of the present invention and within the technical scope, and such modifications and variations all fall within the scope of the claims included in the present invention.

[0164] (Examples and Comparative Examples)

[0165] Example 1

[0166] (1) Preparation of electrode slurry

[0167] In a solvent of ethylene carbonate (EC) and propylene carbonate (PC) with a volume ratio of 5:5, triacrylate (ETPTA) and 2,2'-azobis(isobutyronitrile) (AIBN) were mixed at a weight ratio of 9.9:0.1, and lithium salt LiFSI was dissolved to 1.0M to prepare an electrolyte. The contents of triacrylate (ETPTA) and 2,2'-azobis(isobutyronitrile) (AIBN) in the electrolyte were 9.9 wt% and 0.1 wt%, respectively.

[0168] Artificial graphite as a negative electrode active material and SupreC65 as a negative electrode conductive material were mixed into the electrolyte at a weight ratio of 98:2 to prepare a negative electrode slurry. At this time, the solid content of the negative electrode slurry was 75% and the viscosity at 25°C was 6000 cP.

[0169] In addition, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2 and SuperC65 as a positive electrode conductive material are mixed into the electrolyte at a weight ratio of 97:3 to prepare a positive electrode slurry. In this case, the solid content of the positive electrode electrolyte is 75% and the viscosity at 25°C is 10000 cP.

[0170] (2) Preparation of electrodes

[0171] A copper (Cu) metal film with a thickness of 10 μm was prepared as a negative electrode current collector, and a negative electrode slurry was coated on one side of the copper metal film. The coated negative electrode slurry was covered with a polypropylene film. Then, the negative electrode slurry covered with a polypropylene film (thickness: 100 μm) was hot rolled with a pressing roller with a surface temperature of 60°C. Then, the polypropylene film was peeled off from the electrode, and finally a negative electrode with a total thickness of 85 μm was prepared, in which the negative electrode active material layer and the electrolyte layer were stacked on the negative electrode current collector in sequence.

[0172] An aluminum (Al) metal film with a thickness of 15 μm was prepared as a positive electrode current collector, and a positive electrode slurry was coated on one side of the aluminum metal film. The coated positive electrode slurry was covered with a polypropylene film. Then, the positive electrode slurry covered with the polypropylene film was hot rolled using a pressing roller with a surface temperature of 60°C. Then, the polypropylene film was peeled off from the electrode, and finally a positive electrode with a total thickness of 65 μm was prepared, in which the positive electrode active material layer and the electrolyte layer were stacked on the positive electrode current collector in sequence.

[0173] (3) Manufacturing of lithium secondary batteries

[0174] An electrode assembly in the form of a dual-cell was manufactured by arranging the prepared positive electrode and negative electrode to contact each other in the order of negative electrode / positive electrode / negative electrode.

[0175] The electrode assembly is stored in a battery case and sealed to manufacture a lithium secondary battery.

[0176] Example 2

[0177] An electrode slurry was prepared in the same manner as in Example 1.

[0178] An electrode was manufactured in the same manner as in Example 1, except that a HDPE film was used instead of a polypropylene film.

[0179] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the electrolyte prepared above was used.

[0180] Example 3

[0181] An electrode slurry was prepared in the same manner as in Example 1.

[0182] An electrode was prepared in the same manner as in Example 1, except that after hot rolling using a press roller, the electrode was stored in a room at an internal temperature of 70° C. for 5 hours before the polypropylene film was removed from the electrode.

[0183] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the electrolyte prepared above was used.

[0184] Comparative Example 1

[0185] An electrode slurry was prepared in the same manner as in Example 1.

[0186] An electrode was prepared in the same manner as in Example 1, except that the electrode slurry was hot-rolled using a press roller without covering with a polypropylene film.

[0187] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the electrolyte prepared above was used.

[0188] Comparative Example 2

[0189] An electrode slurry was prepared in the same manner as in Example 1.

[0190] An electrode was prepared in the same manner as in Example 1, except that the electrode slurry was not hot-rolled using a press roller but the polypropylene film was irradiated with ultraviolet rays having a wavelength of 556 nm for 1 minute.

[0191] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the electrolyte prepared above was used.

[0192] Comparative Example 3

[0193] (1) Preparation of electrode slurry

[0194] Artificial graphite as a negative electrode active material, SuperC65 as a negative electrode conductive material, and SBR-CMC as a negative electrode binder were mixed at a weight ratio of 95:1.5:3.5, and water was used as a solvent to prepare a negative electrode slurry. The solid content of the negative electrode slurry was 50%.

[0195] In addition, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, SuperC65 as a positive electrode conductive material, and PVdF as a positive electrode binder were mixed in a weight ratio of 96:1.5:2.5, and NMP was used as a solvent to prepare a positive electrode slurry. The solid content of the positive electrode slurry was 75%.

[0196] (2) Preparation of electrodes

[0197] A copper (Cu) metal film with a thickness of 10 μm was prepared as a negative electrode current collector, and a negative electrode slurry was coated on one side of the copper metal film. Then, the negative electrode slurry was dried and rolled to form a negative electrode active material layer on the negative electrode current collector. The electrolyte prepared in Example 1 was applied to the negative electrode active material layer. The coated electrolyte was covered with a polypropylene film. Then, the electrolyte covered with the polypropylene film was hot rolled using a pressure roller with a surface temperature of 60°C. The hot rolled electrode was stored in a room with an internal temperature of 70°C for 5 hours. Then, the polypropylene film was peeled off from the electrode, and finally a negative electrode with a total thickness of 85 μm was prepared, in which the negative electrode active material layer and the electrolyte layer were stacked on the negative electrode current collector in sequence.

[0198] An aluminum (Al) metal film with a thickness of 15 μm was prepared as a positive electrode current collector, and a positive electrode slurry was coated on one side of the aluminum metal film. The positive electrode slurry was then dried and rolled to form a positive electrode active material layer on the positive electrode current collector. The electrolyte prepared in Example 1 was applied to the positive electrode active material layer. The coated electrolyte was covered with a polypropylene film. Then, the electrolyte covered with the polypropylene film was hot rolled using a pressure roller with a surface temperature of 60°C. The hot rolled electrode was stored in a room with an internal temperature of 70°C for 5 hours. Then, the polypropylene film was peeled off from the electrode, and finally a positive electrode with a total thickness of 65 μm was prepared, in which the positive electrode active material layer and the electrolyte layer were stacked on the positive electrode current collector in sequence.

[0199] (3) Manufacturing of lithium secondary batteries

[0200] A lithium secondary battery was manufactured in the same manner as in Example 1, except that an electrode assembly was prepared by arranging the prepared positive electrode and negative electrode in contact with each other.

[0201] Comparative Example 4

[0202] (1) Manufacturing of positive electrode

[0203] As the positive electrode active material, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, SuperC65 as a positive electrode conductive material, and PVdF as a positive electrode binder were mixed in a weight ratio of 94:3:3, and NMP was used as a solvent to prepare a positive electrode slurry. The solid content of the positive electrode slurry was 50%. The positive electrode slurry was coated on an aluminum (Al) film as a positive electrode current collector, dried and rolled to prepare a positive electrode.

[0204] (2) Manufacturing of negative electrode

[0205] Artificial graphite as a negative electrode active material, SuperC65 as a negative electrode conductive material, and SBR-CMC as a negative electrode binder were mixed in a weight ratio of 96:2:2, and water was used as a solvent to prepare a negative electrode slurry. The solid content of the negative electrode slurry was 80%. The negative electrode slurry was coated on a copper (Cu) film as a negative electrode current collector, dried and rolled to prepare a negative electrode.

[0206] (3) Preparation of electrode assembly

[0207] The electrode assembly is prepared by sequentially stacking the positive electrode, separator and negative electrode prepared above. The separator adopts a three-layer stacking structure of polypropylene / polyethylene / polypropylene.

[0208] (4) Manufacturing of lithium secondary batteries

[0209] The electrode assembly was inserted into a pouch-type battery case, and the electrolyte prepared in Example 1 was injected therein. The battery case was sealed under vacuum. The sealing was performed by pressurizing the sealed portion of the bag at 140° C. for 2 seconds. After the battery case was sealed, the case was left at room temperature for 3 days and heated in a heating chamber at 70° C. for 5 hours to prepare a lithium secondary battery containing a thermally polymerized gel polymer electrolyte.

[0210] [Table 1]

[0211]

[0212] Experimental Example 1 - Evaluation of Adhesion of Electrode Active Material Layer

[0213] For the positive electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 4, 180° peel strength of the active material layer was measured.

[0214] Specifically, the positive electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were cut into 20 mm widths, respectively. Then, the positive electrode active material layer was peeled off from the positive electrode current collector using a UTM device, and the average value of the 180° peel strength within a displacement range of 20 mm to 80 mm was measured. Figure 2 And Table 2 shows the measurement results.

[0215] Figure 2 : is a graph measuring the adhesion between the active material layer and the current collector in the positive electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 4, respectively.

[0216] Experimental Example 2 - Evaluation of Electrode Stiffness

[0217] The stiffness of the positive electrodes and negative electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 4, respectively, was measured.

[0218] Specifically, for the positive and negative electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 4, respectively, the electrodes were fastened to an aluminum (Al) fixture having a hole with a diameter of 5 cm, and then the electrodes were pressed with a metal rod with a diameter of 2 cm using a UTM device. The measurement results are shown in Table 2 below.

[0219] Experimental Example 3 - Electrolyte Leakage during Lithium Secondary Battery Manufacturing

[0220] In the process of manufacturing the lithium secondary batteries in Examples 1 to 3 and Comparative Examples 1 to 4, whether the electrolyte solution leaked from the electrode assembly was detected and is shown in Table 2 below.

[0221] O: Electrolyte leakage

[0222] X: No electrolyte leakage

[0223] Experimental Example 4: Evaluation of Lithium Secondary Battery Capacity

[0224] The capacity of the lithium secondary batteries manufactured in Examples 1 to 3 and Comparative Examples 1 to 4 was measured. Specifically, the lithium secondary batteries were fastened to an aluminum fixture using a PNE solution charge / discharge device, and then charged / discharged according to the following conditions to measure the battery capacity. The measurement results are shown in Table 2 below.

[0225] Charging conditions: Charging at a rate of 0.2C in CC (constant current) / CV (constant voltage) mode, with a cutoff of 4.2V and 0.05C.

[0226] Discharge conditions: Discharge at a rate of 0.2C in CC mode and cut off at 3.0V.

[0227] Experimental Example 5-Evaluation of the Lifespan of Lithium Secondary Batteries

[0228] The lithium secondary batteries manufactured in Examples 1 to 3 and Comparative Examples 1 to 4 were charged / discharged at 45° C. according to the following conditions, and the capacity retention rate depending on the number of cycles was measured.

[0229] Charging conditions: Charging at a rate of 0.33C in CC (constant current) / CV (constant voltage) mode, with a cutoff of 4.2V and 0.05C.

[0230] Discharge conditions: Discharge at a rate of 0.33C in CC mode and cut off at 3.0V.

[0231] In this case, the battery capacity retention rate was measured using JEIO TECH's IL-2C-525S. Figure 3 And Table 3 shows the measurement results.

[0232] Figure 3 : is a graph showing the capacity retention rate of the lithium secondary batteries manufactured in Examples 1 to 3 and Comparative Examples 1 to 4 as a function of the number of cycles after being driven at 45°C.

[0233] [Table 2]

[0234]

[0235] [Table 3]

[0236]

[0237] like Figure 2 and Figure 3 As shown in Tables 2 and 3, compared with Comparative Examples 1 to 4, the lithium secondary batteries of Examples 1 to 3, whose electrode active material layers contain electrode active materials and gel polymer electrolytes and satisfy the electrode stiffness range of the electrode active material layers, have no electrolyte leakage, excellent capacity performance, and remarkably excellent life performance.

[0238] like Figure 2As shown in Table 2, it can be seen that the electrode active material layers of Examples 1 to 3 in which the oxygen barrier member was provided and heat-rolled have significantly superior adhesion compared to Comparative Example 1 in which the oxygen barrier member was not used and Comparative Example 2 in which UV curing was performed instead of heat curing by heat rolling. In Examples 1 to 3, it can be seen that the electrolyte in Example 3 was additionally heat-cured in a high temperature chamber, so that the adhesion of the electrode active material layer thereof was stronger than that of Examples 1 and 2.

[0239] In Comparative Example 1 in which no oxygen barrier member was used, the electrode slurry was exposed to oxygen, so the electrolyte in the electrode was not cured even after hot rolling. Since the polymer in the electrolyte was not cured, it could not function as a binder, and therefore, the adhesion of the electrode active material layer of Comparative Example 1 was significantly reduced compared to Examples 1 to 3.

[0240] In Comparative Example 2, in which UV curing was performed without hot rolling, only the electrolyte disposed on the upper portion of the electrode active material layer was cured, while the electrolyte disposed on the lower portion of the electrode active material layer was not cured. Therefore, the active material layer was separated at the boundary between the upper layer and the lower layer of the electrode active material layer, and thus the adhesion of the electrode active material layer of Comparative Example 2 was significantly reduced compared to Examples 1 to 3.

[0241] Meanwhile, as shown in Table 2, the electrode active material layers of Examples 1 to 3 in which the oxygen barrier member was provided and heat-rolled had significantly superior stiffness compared to Comparative Example 1 in which the oxygen barrier member was not used and Comparative Example 2 in which UV curing was performed instead of heat curing by heat rolling. Among Examples 1 to 3, the electrolyte in Example 3 was additionally heat-cured in a high temperature box, and it had a stronger stiffness of the electrode active material layer than Examples 1 and 2.

[0242] In Comparative Example 1 in which no oxygen barrier member was used, the electrode slurry was exposed to oxygen, and thus did not solidify even after the electrolyte in the electrode was hot rolled. Therefore, the electrode rigidity was significantly reduced compared to Examples 1 to 3.

[0243] In Comparative Example 2, in which UV curing was performed instead of heat rolling, the electrolyte provided on the electrode surface was cured, while the electrolyte provided inside the electrode was not cured. Therefore, the electrode rigidity was significantly reduced compared with Examples 1 to 3.

[0244] Meanwhile, as shown in Table 2, it can be seen that in Comparative Example 1 in which no oxygen barrier member was used and Comparative Example 2 in which UV curing was performed instead of heat curing by hot roller pressing, the electrolyte in the electrode was not sufficiently cured, and thus the electrolyte leaked from the electrode assembly during battery assembly.

[0245] At the same time, if Figure 3As shown in Tables 2 and 3, it can be seen that in Comparative Example 3 in which the conventional electrode was impregnated with an electrolyte and then thermally cured, the electrolyte was not impregnated into the interior of the electrode, and therefore no thermally cured electrolyte existed inside the electrode. Accordingly, the battery capacity and battery capacity retention rate of Comparative Example 3 were significantly reduced compared with Examples 1 to 3.

[0246] In addition, in Comparative Example 4, unreacted monomers were present in the gel polymer electrolyte or the electrode was not sufficiently impregnated with the gel polymer electrolyte, resulting in low electrode rigidity, thereby exhibiting low capacity and reduced life performance.

[0247] [Explanation of Reference Numerals]

[0248] 10: Electrode

[0249] 110: Current collector

[0250] 120: Electrode active material layer

[0251] 130: coating (or electrolyte layer)

Claims

1. An electrode, comprising: Electrode current collector; as well as an electrode active material layer disposed on at least one side of the electrode current collector, wherein the electrode active material layer comprises an electrode active material and a gel polymer electrolyte, and The stiffness of the electrode is 2 kPa to 4 kPa.

2. The electrode according to claim 1, wherein The gel polymer electrolyte is impregnated in the electrode active material layer.

3. The electrode according to claim 1, wherein The electrode is a positive electrode, The electrode active material is a positive electrode active material, and The positive electrode active material includes a lithium nickel cobalt composite oxide represented by the following formula 1: [Formula 1] Li 1+x (Ni a Co b Mr c M d )O2 Among them, in the above formula 1, M is at least one selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and 1+x, a, b, c and d are the molar ratios of the independent elements respectively, and satisfy -0.2≤x≤0.2, 0.60≤a<1, 0 <b≤0.30,0<c≤0.30,0≤d≤0.10,a+b+c+d=1。 4. The electrode according to claim 1, wherein The electrode is a negative electrode, The electrode active material is a negative electrode active material, and The negative electrode active material is a carbon material.

5. The electrode according to claim 1, wherein The gel polymer electrolyte is a solidified product of an electrolyte solution containing a cross-linkable material, a lithium salt and an organic solvent; and The cross-linkable material includes at least one selected from a cross-linkable monomer and a cross-linkable oligomer.

6. The electrode according to claim 1, wherein The electrode active material layer further comprises a coating layer disposed on a side opposite to a side facing the electrode current collector, and The coating contains a gel polymer electrolyte.

7. A method for manufacturing an electrode, the method comprising: applying an electrode slurry containing an electrolyte onto an electrode current collector; disposing an oxygen barrier member on the applied electrode slurry; as well as The electrode slurry covered with the oxygen barrier member is subjected to hot roll pressing. The electrolyte is thermally cured by hot roller pressing.

8. The method of claim 7, wherein: The hot rolling includes rolling the electrode slurry with a rolling roller having a surface temperature of 30°C to 80°C.

9. The method of claim 7, wherein: The thickness of the electrode after hot rolling is 50 μm to 1000 μm.

10. The method of claim 7, wherein: The oxygen blocking member includes a material having flexibility.

11. The method of claim 10, wherein: The oxygen barrier member includes at least one selected from the group consisting of polypropylene (PP) and high-density polyethylene (HDPE).

12. The method of claim 7, wherein: The method further comprises heating the electrode after hot rolling, The electrolyte in the electrode is additionally thermally cured by heating.

13. The method of claim 12, wherein: The heating includes storing the electrode at a temperature of 40° C. to 80° C. for 10 minutes to 24 hours.

14. The method of claim 7, wherein: The electrode slurry is prepared by mixing an active material and a conductive material with an electrolyte.

15. The method of claim 7, wherein: The electrode slurry does not contain a binder and N-methyl-2-pyrrolidone (NMP).

16. The method of claim 7, wherein: The electrolyte includes at least one of a monomer and an oligomer in an amount of 4 wt % to 40 wt %.

17. The method of claim 16, wherein: The monomer includes at least one selected from the group consisting of ethylene glycol diacrylate, triethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate (ETPTA), bisphenol A ethoxylated dimethacrylate, acrylic acid, carboxyethyl acrylate, methyl cyanoacrylate, ethyl cyanoacrylate, ethyl cyanoethoxyacrylate, cyanoacrylic acid, hydroxyethyl methacrylate and hydroxypropyl acrylate.

18. The method of claim 16, wherein: The oligomer includes at least one selected from the group consisting of polyether oligomers, polycarbonate oligomers, acrylate oligomers, polysiloxane oligomers, phosphazene oligomers, polyethylene oligomers, polyurethane oligomers, epoxy oligomers, fluorine oligomers, polyethylene oxide, polyester sulfide, polyvinyl alcohol and polyvinylidene fluoride. A lithium secondary battery comprising the electrode according to claim 1 .

Citation Information

Patent Citations

  • Advertising system for self driving cars

    KR1020220109522A